THE CONCEPT AND RESEARCH OF PRECEDENT NAME - Kholnazarov Umid Erkinovich (Web of Journals Publishing, 2024)
This article is based on the fact that precedent names, as units of language and speech, are a linguistic and cultural process that occurs as a result of the communication of representatives of different languages, as a sum of the national-cultural worldview, national character, lifestyle and values of each people.
Keywords: Precedent name, metaphor, national linguistic representation of the world, color, linguistic and cultural process, cognitive and emotional attitude, intertextuality